Verbes de perception sensorielle comme introducteurs des paroles représentées - Elżbieta Biardzka; Greta Komur-Thilloy (Studia Linguistica)
The subject of this study are the sequences of reported speech with verbs of sensory perception. Our objective is to characterize these forms to place them in the reported speech system. Our analysis is inspired by the descriptions contained in the recent work by Jacqueline Authier-Revuz (2020) which offers a differential approach to the forms of the reported speech. We would like to show in particular that the direct speech containing the verbs of sensory perception is distinguished by important enunciative and syntactic particularities. This is why we can ask ourselves whether it is a clear and simple form of the reported speech or, linked to the appearance of the verbs of sensory perception, it falls within the scope of the reported speech as a ‘variant’ of the DD in addition.